Diversity of Echinoderms on the Beach of Ranowangko II Village, Kombi District, Minahasa Regency - Letsoin, Imanuel Junisa Adolfina; Rampengan, Mercy Maggy Franky; Roring, Verawati Ida Yani; Lawalata, Helen Joan (RUMPHIUS, 2024)
This research is motivated by the lack of studies and absence of research data on the diversity of Echinoderms on the Beach of Ranowangko II Village, Kombi District, Minahasa Regency. The aim of this study is to determine the diversity of the phylum Echinodermata found on the Beach of Ranowangko II Village, Kombi District, Minahasa Regency. Sampling in this research used the quadrat transect method with 3 transect lines, each line being 100 m long, and 10 quadrats, each measuring 1 x 1 m². The results of the study found 4 classes and 5 species including the class Asteroidea (Protoreaster nodosus), class Ophiuroidea (Ophiocoma scolopendrina), class Echinoidea (Tripneustes gratilla), class Holothuroidea (Holothuria atra & Holothuria vagabunda), and there were 21 individuals, and the dominant species is Holothuria atra from the Holothuroidea class of which there are 11 individuals, indicating that the diversity index (H’) of the phylum Echinodermata on the location is moderate with a value of 1.204. These findings offer initial insights into the condition of the local ecosystem, classified as moderate, and may serve as a foundational reference for long-term ecological monitoring.